2018
DOI: 10.1371/journal.pone.0190881
|View full text |Cite
|
Sign up to set email alerts
|

Do blast induced skull flexures result in axonal deformation?

Abstract: Subject-specific computer models (male and female) of the human head were used to investigate the possible axonal deformation resulting from the primary phase blast-induced skull flexures. The corresponding axonal tractography was explicitly incorporated into these finite element models using a recently developed technique based on the embedded finite element method. These models were subjected to extensive verification against experimental studies which examined their pressure and displacement response under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 63 publications
3
15
0
Order By: Relevance
“…The larger peak-pressure discrepancy between our study and Garimella et al could be due to the differences in the algorithm implemented to apply the blast load to the head. Similar to Sharma (2011) and Garimella et al (2018), we observed oscillations in the simulated pressuretime profiles compared to the experimental values. These oscillations in the frontal lobe could be possibly attributed to the blast wave continuously deforming the skull as it propagates through the head (Garimella et al, 2018;Moss et al, 2009) as well as reflections from the skin-skull, skull-subarachnoid space, and subarachnoid space-brain interfaces (Ganpule et al, 2013).…”
Section: Model Validation and Pressure Amplificationsupporting
confidence: 87%
See 2 more Smart Citations
“…The larger peak-pressure discrepancy between our study and Garimella et al could be due to the differences in the algorithm implemented to apply the blast load to the head. Similar to Sharma (2011) and Garimella et al (2018), we observed oscillations in the simulated pressuretime profiles compared to the experimental values. These oscillations in the frontal lobe could be possibly attributed to the blast wave continuously deforming the skull as it propagates through the head (Garimella et al, 2018;Moss et al, 2009) as well as reflections from the skin-skull, skull-subarachnoid space, and subarachnoid space-brain interfaces (Ganpule et al, 2013).…”
Section: Model Validation and Pressure Amplificationsupporting
confidence: 87%
“…The three key attributes of our 3-D high-fidelity human-head FE model are 1) the detailed network of cerebral veins and arteries (Figure 1), 2) the representation of the brain-tissue gyri and sulci, and 3) the hyper-viscoelastic material properties to model blastinduced brain-tissue deformations (Table 1). In contrast, Sharma (2011), Singh et al (2014), and Panzer et al (2012, who developed coupled FE models similar to our study, and Garimella et al (2018), who applied a blast load to a humanhead FE model using the Conventional Weapons Program (Hyde, 1991), did not model the cerebral vasculature or the brain-tissue gyri and sulci. Moreover, Sharma (2011), Singh et al (2014), andPanzer et al (2012) employed linear viscoelastic brain-tissue properties, whereas Garimella et al (2018) used hyperviscoelastic material properties to model blast-induced braintissue deformations.…”
Section: Comparison Of Model Featuresmentioning
confidence: 81%
See 1 more Smart Citation
“…Factors associated with biomechanical differences related to scaling, sex, and age are also of relevance. For example, blast effect sex differences for human males and females have received little attention, but—while there is significant overlap—there are reported average differences in size and skull thickness that can have different consequences on skull flexure during shock wave loading ( 211 213 ). Likewise, the skull shape differences are significantly dissimilar for different species used in preclinical study ( 214 ), for the determination of sex differences in primates, but mouse differences appear to be trivial ( 215 ).…”
Section: Preclinical Modeling Of Blast For the Study Of Sex Differencmentioning
confidence: 99%
“…(Tanielian, 2008;Warden, 2006) Understanding how the blast wave interacts with the head-brain parenchyma is crucial for devising blast mitigation strategies, clinical interventions, therapeutics, and recreating injury in a laboratory. Several mechanisms of blast induced traumatic brain injury have been proposed, including direct intracranial transmission, (Nyein et al, 2010;Sundaramurthy et al, 2012;Taylor and Ford, 2009) skull flexure, (Bolander et al, 2011;Garimella et al, 2018;Moss et al, 2009) a thoracic mechanism, (Cernak et al, 2001;Simard et al, 2014) cavitation, (Panzer et al, 2012;Salzar et al, 2017) and head acceleration. (Goldstein et al, 2012;Gullotti et al, 2014) Yet, the current understanding of the contribution of each mechanism in generating mechanical fields within the brain is limited (Fievisohn et al, 2018;Meaney et al, 2014) and findings in the literature are contradictory.…”
Section: Introductionmentioning
confidence: 99%